ORGANIZATIONAL DEVELOPMENT THROUGH KNOWLEDGE MANAGEMENT - Surabhi Deshpande (Jurnal Ilmiah Ekonomi Bisnis, 2012)
As organizations grow in size, geographical scope, and complexity, it is increasingly apparent that sponsorship and support of communities of practice—groups whose members regularly engage in sharing and learning, based on common interests—can improve organizational performance.   Keywords: Knowledge management, Management Organisation